Determination of permeability profile of soft Rangsit clay by field and laboratory tests - Ahmed, Md. Mesbahuddin; Holmberg, Soren; Brand, E.W.; Balasubramaniam, A.S.; Government of British Colombia (Bangkok : Asian Institute of Technology, 1977)
This thesis presents the results from a field and laboratory investigation of the permeability of the soft Rangsit Clay. The field investigation included constant head permeability tests by means of piezometers installed at different depths. In the laboratory, the vertical and horizontal coefficient of permeability were determined both from constant head permeameter tests and from conventional consolidation tests. Except for the drying crust and a sandy clay layer below the soft clay deposit there was surprisingly little difference between the results obtained by the different types of tests. It, therefore, seems reasonable for most practical purposes at least, to determine the permeability by means of consolidation tests. The use of back pressuring the specimens when testing in the permeameter was investigated.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Clay -- Testing